Film as Embodied Art Bodily Meaning in the Cinema of Stanley Kubrick - Coëgnarts, Maarten (Academic Studies Press, 2019)
How do the visuals of Kubrick's work convey complex concepts and abstractions without the traditional reliance on words? And how does the pure instrumental music in his films express meaning when music, in essence, is an abstract art form? Drawing on state-of-the-art research in embodied cognitive science, this book sets out to explore these questions by revealing Kubrick as a genuine conceptual artist, a filmmaker who perhaps more than any other director, uses all the non-verbal resources of filmmaking in such a controlled and dense manner as to elicit the bodily structures necessary to achieve a level of conceptual understanding.